KUALITAS DAN UMUR SIMPAN TEPUNG TALAS DENGAN TEKNIK PENGERINGAN YANG BERBEDA - Sastika, Nadhiya; Fridayati, Lucy; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2017)
This research was motivated by their calcium oxalate in the taro that can cause itching, irritation of the skin, mouth, throat and gastrointestinal tract when consumed directly. While we know that taro can be processed into flour with low water levels that extend the shelf life. This study aimed to analyze the quality (color, aroma, texture) and shelf life taro flour with hot sun and drying techniques oven. Type of research is pure experiment using a completely randomized design. This study was conducted on 21 November to 5 January 2017 in the workshop culinary art department of IKK, FPP, UNP. The instrument used is the format of organoleptic tests given to five expert panelists. Data were tabulated and analyzed using independent sample t test. The results showed that there was no significant effect of these two different drying techniques on the quality and shelf life, taro flour for T arithmetic < T table. Keywords : Shelf Life, Taro Flour, Drying